Почвы черневой тайги Западной Сибири - морфология, агрохимические особенности, микробиота - Абакумов, Евгений Васильевич; Лойко, Сергей Васильевич; Истигечев, Георгий Игоревич; Кулемзина, Анастасия Игоревна; Лащинский, Николай Николаевич младший 1960-; Андронов, Евгений Евгеньевич; Лапидус, Алла Львовна (Сельскохозяйственная биология)
The soils of Chernevaya taiga are unique in terms of high fertility that was formed not as a result of agricultural practices, but due to the combination of a huge volume of biotic and abiotic resources. This area was able to preserve its "pre-agricultural" level of fertility overtime by avoiding the negative consequences of long-standing agricultural usage. Comprehensive analysis of all related properties within the framework of a metagenomic study and identification of microbial drivers of fertility can become the basis for innovative technologies aimed to increase the productivity of soils and crops. In this work, for the first time were obtained data on the taxonomic structure and features of the microbiota of soils in the Chernevaya taiga and identified taxa, the number of which significantly increases with the transition from the mature zonal soil to the soil of Chernevaya taiga. Analysis of soil samples collected during expeditionary surveys in 2019 showed that the soils in the Western Siberia (Novosibirsk, Tomsk, Kemerovo, and Altai regions) portion of the Chernevaya taiga are texture-differentiated dark gray soils (clay loam and silt clay varieties confined to the deluvial cover of the Holocene and Late Pleistocene) that were formed as a result of a unique combination of geogenic and bioclimatic conditions. These soils are not affected by the permafrost in winter timers and are supplied with enough moisture to precipitate rapid mineralization of litter material and the fixation of mineral nutrients in the upper humus layer of the soil profile. The accumulation of nutrients is an essential property of the soils of the Chernevaya taiga associated with the phenomenon of gigantism and extremely high levels of plant productivity. The soils of Chernevaya taiga contain the maximum amount of carbon in organic compounds compared with soils of oligotrophic habitats (9.85% versus 2.74%). The levels of actual soil fertility in the soils of the Chernevaya taiga are several times higher than in the soils of adjacent biotopes (the maximum content of the exchange forms of phosphorus and potassium is 702 and 470 mg/kg), which, when compared to oligotrophic forests, are poor in terms of agrochemical fertility (the maximum content of the exchange forms of phosphorus and potassium is 113 and 18 mg/kg), do not have a pronounced humus profile and are either gray-humus (Umbrisol) or Podzol types according to substantive-profile classification of Russian soils. The diversity of microorganisms in the studied soils varies depending on the trophic regime of the ecosystem. The soils of the Chernevaya taiga are characterized by an increased diversity of the microbial community (estimated 1019 by the Shannon index), as well as by presence of phyla Nitrospirae and Thaumarchaeota, that, however, are not dominant. Phyla Proteobacteria, Verrucomicrobia, Actinobacteria, Acidobacteria, Planctomycetes, Firmicutes appeared to be common for all studied soils.